Analisis Daya Dukung Tanah Dasar terhadap Kerusakan Jalan Raya Pule-Sarirejo - Pratama, Yudha Putra; Dhana, Rio Rahma (Universitas Batanghari Jambi, 2024)
Roads are the main function as infrastructure for all forms of land transportation. For those who use the road, because a good road has a beneficial influence on the community, the road serves as the main foundation for economic turnover activities and social activities of the community. So comfort and tranquility when driving are very important factors before the construction of road pavement construction, the stability of a road must first be known the carrying capacity of the soil as a foothold. The carrying capacity of the soil that damages the pule-sarirejo road was evaluated by researchers. Factors affecting the decrease in soil carrying capacity were also studied in this study. Testing water content with an average value of 15.39% which includes high water content, data processing shows that the road bottom soil on Jalan Pule – Sarirejo has a low carrying capacity value in this test. For testing the boundaries Atterberg belongs to the group of clay soil types. with a PI value of 58.85% has a high platicity value. However, it is known from the results of CBR testing that the CBR value of the road base soil is 7.00%, included in the